2010
DOI: 10.1007/s00402-009-1041-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cervical nucleoplasty and percutaneous cervical discectomy treatments of the contained cervical disc herniation

Abstract: PCN and PCD treatments of contained cervical disc herniation show good outcomes and there was no difference in the stability of cervical spine. PCN and PCD are safe, minimally invasive, and no differences were observed between the methods in clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 22 publications
1
52
0
1
Order By: Relevance
“…Within this group, pain medication use was diminished in 79% of the cases, and almost two‐thirds of all patients did not use any pain medication at all after treatment (63%). The low complication rate found in our study is comparable to findings of several other studies . Gertszen et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Within this group, pain medication use was diminished in 79% of the cases, and almost two‐thirds of all patients did not use any pain medication at all after treatment (63%). The low complication rate found in our study is comparable to findings of several other studies . Gertszen et al .…”
Section: Discussionsupporting
confidence: 92%
“…Several techniques are used in the treatment for cervical disk herniation . In the past, conventional cervical discectomy was considered the standard treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of RF, reports have shown high patient satisfaction, with 77% to 83% excellent or good results, according to the MacNab criteria. [13][14][15]18 For VAS, Sim 18 reported an improvement from 9.3 to 3.4 at the six-month follow-up, and Schubert showed an improvement from 8.3 to 2.5 in a two-year follow-up. 19 Likewise, the use of laser -an analogous technology to the RF used in this study -showed satisfaction rates of around 50% 20 and 90%.…”
Section: Discussionmentioning
confidence: 96%
“…In 2007; however, it was reported to develop epidural fibrosus following nucleoplasty [34]. Another study conducted on human cadavers demonstrated that lethal thermal damage might develop outside the nucleus pulposus due to misplacement of the radio frequency probe [35], but other studies showed that PN was safe, with very little complication risk [3336]. …”
Section: Discussionmentioning
confidence: 99%